2007
DOI: 10.1002/lsm.20508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐level laser treatment after installation of dental titanium implant‐immunohistochemical study of RANKL, RANK, OPG: An experimental study in rats

Abstract: From the above results, the expression of OPG, RANKL, and RANK during the osseointegration of the dental titanium implant was observed within bone tissue. The application of the LLL influenced the expression of OPG, RANKL, and RANK, and resulted in the expansion of metabolic bone activity and increased the activity of bone tissue cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 27 publications
(28 reference statements)
3
42
1
4
Order By: Relevance
“…Despite the fact that lasers have demonstrated efficiency on osseous tissue healing [4,[10][11][12][13][14], in implantology, factors like high initial stability, implant geometry, and good bone quality, are more relevant for the quality of the implantbone interface than any additional therapeutic effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that lasers have demonstrated efficiency on osseous tissue healing [4,[10][11][12][13][14], in implantology, factors like high initial stability, implant geometry, and good bone quality, are more relevant for the quality of the implantbone interface than any additional therapeutic effort.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that bone irradiated mostly with infrared wavelengths shows increased osteoblastic proliferation, collagen deposition, and bone neoformation when compared to non-irradiated bone [10][11][12][13]. Little data exist concerning these effects on the osseointegration process of implants [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These procedures would not be possible in rats or mice. 9,10,13,40 In accordance with the most recent literature, LLLT was delivered by an infrared laser [7][8][9][10][11][12][13][14][15][26][27][28]35,38 of 830 nm wavelength 7,10,[12][13][14][15] and 50 mW output power in two sites near the mandibular implant, in seven sessions 7,11,12,15 every 48 h, using three different doses. The use of a sham surgery and sham LLLT control group (C-I), as well as a baseline surgery but sham LLLT group (C-II), enabled us to isolate both the influence of baseline surgery and the systemic effects of LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the irradiation of extraction sockets, 3 modulation of skin wound healing, [4][5][6] regeneration of nervous tissue, 5 enhancement of peri-implant tissue repair after implant placement, 2,[7][8][9][10][11][12][13][14][15][16] and modulation of postoperative pain. 2,7,[17][18][19][20][21][22][23][24] Other in vivo and in vitro studies have reported the positive effects of LLLT on the repair process in animal models and tissue cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation